Pembelajaran Multikultur Melalui Edutainment di Galeri Indonesia Kaya - Ceria Isra Ningtyas (Jurnal Manajemen dan Kearifan Lokal Indonesia, 2018)
Today, the multicultural education in traditional games can be packed together with information and communication technology. This can lead to greater curiosity from the younger generation to learn multiculturalism in Indonesia by using gadgets that educating also entertaining. The location of the research was conducted at Galeri Indonesia Kaya (GIK) located at Grand Indonesia Mall, Central Jakarta. The aims of this research are (1) exploring multicultural learning through edutainment in GIK and (2) explaining the multicultural communication perspective shown in GIK. This study uses a qualitative descriptive approach. Data collection techniques use the interview data and some literature review. The results of the study are as follows (1) GIK visitors are very impressed with the presentation of cultural information and experienced different ambience of multicultural learning because studying Indonesian culture now is no longer monotonous but very easy and fun. This is because delivering Indonesian cultural knowledge in GIK use many interactive applications that support multicultural learning through edutainment; and (2) GIK presents several perspectives of multiculturalism communication, ie (a) inclusive/the value of openness; (b) the value of prioritizing the dialogue actively; (c) the value of humanity; (d) the value of fairness; (e) the value of equality and fraternal brotherhood; and (f) the value of loving the homeland